Employment mobility and pay for sector performance - Liu, Yun; Nanda, Vikram; Onal, Bunyamin; Silveri, Sabatino (Journal of Corporate Finance, 2021)
We argue that executives' employment mobility significantly affects their pay for sector performance. In particular, as executives' outside employment options increase with social connections we hypothesize that better-connected executives receive greater pay for sector performance. Supportive of our hypothesis, we find that pay for sector performance is more pronounced when executives are better connected, both within and across industries. Further, intra-industry connections have a stronger effect when enforceability of non-compete agreements is weaker. While the prior literature finds that social networks impact the level of CEO pay through an information channel, our findings suggest that social networks also impact pay for sector performance through an outside employment options channel.